A Systematic Review of the Association of Preoperative Optimization of Diabetic Patients with Perioperative Glycemic Control and Postoperative Outcomes - Pretika Prameswari; Raka Jati Prasetya; Mutia Juliana (International Medical Journal Corp. Ltd, 2025)
Introduction: The prevalence of diabetes mellitus (DM) in surgical populations is substantial and represents a significant independent risk factor for postoperative complications. Preoperative optimization of glycemic control has emerged as a key strategy to mitigate these risks by improving patients' physiological resilience to surgical stress. This review systematically evaluates the association between preoperative glycemic status and postoperative outcomes. Methods: A systematic search of PubMed and the Cochrane Library was conducted for studies published through 2024. Inclusion criteria specified randomized controlled trials and observational studies evaluating preoperative glycemic markers (e.g., glycated hemoglobin ( HbA1c ), blood glucose) or structured optimization interventions in adult diabetic patients undergoing surgery. Primary outcomes included surgical site infection (SSI), 30-day mortality, and major adverse cardiovascular events (MACE). Secondary outcomes included length of stay (LOS), acute kidney injury (AKI), and other morbidities. Study quality was appraised using the Cochrane Risk of Bias 2 and ROBINS-I tools. Results: Seventeen studies, encompassing randomized trials and large cohort analyses, met the inclusion criteria. The evidence consistently links poor preoperative glycemic control, indicated by elevated HbA1c or acute hyperglycemia, with a significantly increased risk of postoperative complications. Specifically, high HbA1c levels were strongly associated with higher rates of SSI (Odds Ratio ranging from 2.13 to 3.0) and prolonged hospital LOS. Acute perioperative hyperglycemia was a more direct predictor of MACE and mortality (Hazard Ratio 1.26 for adverse cardiac events). Structured interventions, such as multidisciplinary preoperative clinics, demonstrated efficacy in reducing preoperative HbA1c levels, particularly in patients with the poorest baseline control. Discussion: The synthesized evidence highlights a critical debate regarding the predictive primacy of chronic ( HbA1c ) versus acute (perioperative blood glucose) hyperglycemia. While acute hyperglycemia appears to be the more proximate driver for immediate adverse events like myocardial injury, HbA1c serves as an essential tool for risk stratification, identifying patients who will benefit most from intensive perioperative management. The heterogeneity of the existing literature, particularly the scarcity of high-quality randomized trials, underscores the complexity of this issue. Conclusion: Poor preoperative glycemic control is unequivocally associated with adverse postoperative outcomes in diabetic patients. While the optimal strategy for preoperative optimization remains to be defined by high-quality evidence, current data support a shift from using HbA1c as a rigid surgical gatekeeper to a trigger for activating comprehensive, multidisciplinary perioperative management pathways.